If evidence matters, why does the data die? Implementing education management information systems (EMIS) in development contexts - El Mazbouh, Manal; Shah, Ritesh; Lee, Kerry (Frontiers in Education, 2025)
Over the last three decades, international organizations have been increasingly involved in collecting and utilizing data to enhance data-driven decision making in the education sectors of development contexts. This is carried out mainly through Education Management Information Systems (EMIS). Research shows, however, that while EMIS have managed to capture large amounts of data in such contexts, evidence of the use of data towards improvement of outcomes is sparse at best, with persistent reports that EMIS data is underutilized nationally. This article relies on documentary data and key informant interviews to explore the reasons for this failure of utility, critically examining the mechanisms underpinning the continued challenges to the utilization of EMIS data in development contexts. The data is analyzed using a reflexive thematic analysis approach from a critical realist lens, interweaving literature, data and inquiry to raise critical questions about and offer potential explanations as to why the data dies. This work reveals three profoundly contextual mechanisms operating within the structure of the ‘development project:’ (1) a Eurocentric notion of the generalizability of EMIS systems; (2) an enduring colonial mindset that considers educational data another resource that can be extracted and used; and (3) a devaluation of people from such contexts- as entities with agency and rights - in favor of data.